2008
DOI: 10.2174/092986608783489553
|View full text |Cite
|
Sign up to set email alerts
|

High Yield Expression of Human BACE Constructs in Eschericia coli for Refolding, Purification, and High Resolution Diffracting Crystal Forms

Abstract: BACE (beta-site APP cleaving enzyme) or beta-secretase, the enzyme responsible for processing APP to give the N-terminal portion of the Abeta peptide, is a membrane bound aspartyl protease consisting of an ectodomain catalytic unit, a C-terminal transmembrane segment and a cytoplasmic domain. Three BACE constructs, pET11a-BACE, pQE80L-BACE, and pQE70-BACE were designed to terminate at a position just before the transmembrane domain (Ser(432)) and are described schematically below. (1) pET11a-T7.Tag-G-S-M-(A-8G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…This study has been performed with the aim of obtaining information about the structural characteristics responsible for the anti‐HIV activity of this class of compounds, that is, to understand the effect of substitution on their inhibitory activity using Kier‐Hall E‐state indices. Also, the study is aimed at determining QSAR of HIV‐1 NNRTIs for the class of TIBO1, 4 and its derivatives 18. E‐state indices for various functional groups (namely, E X‐8 , E Z‐O , E Z‐S, E R , E X′‐7 , E X′‐di , E N , E NR ) are calculated using e‐calc 40.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has been performed with the aim of obtaining information about the structural characteristics responsible for the anti‐HIV activity of this class of compounds, that is, to understand the effect of substitution on their inhibitory activity using Kier‐Hall E‐state indices. Also, the study is aimed at determining QSAR of HIV‐1 NNRTIs for the class of TIBO1, 4 and its derivatives 18. E‐state indices for various functional groups (namely, E X‐8 , E Z‐O , E Z‐S, E R , E X′‐7 , E X′‐di , E N , E NR ) are calculated using e‐calc 40.…”
Section: Methodsmentioning
confidence: 99%
“…The human immunodeficiency virus (HIV‐1)1–5 is the causative agent of the dreaded global disease, acquired immunodeficiency syndrome (AIDS), which was first detected in mid‐1980s 6. It is now recognized that the immune deficiency is a consequence of continuous high‐level HIV replication leading to an increased impairment of cell‐mediated immunity due to gradual attrition of the key immune effector cell, the CD4 lymphocyte 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was shown that although BACE knockout mice have reduced Ab production, they do not exhibit any abnormal phenotypes (Luo et al 2001). The BACE gene was cloned and characterized in 1999 (Vassar et al 1999), and various BACE constructs have been expressed in insect (Bruinzeel et al 2002), mammalian , and E. coli cells (Sardana et al 2004;Tomasselli et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to the current literature, purifying BACE1 using an E. coli expression system requires either multiple, pHadjusted refolding steps 18 or a particular affinity column for purification. 19 Overall, the protein yield ranges from 1 to 8 mg from 1 L of culture. Here, a relatively simple refolding and purification method.…”
mentioning
confidence: 99%